DISAPPROVED GROUP BEHAVIORS WITHIN THE POLICE FORCE - Eugeniusz MOCZUK (Humanities and Social Sciences)
The Police Force, as a social institution, is not immune to various types of socially unacceptable behavior. Such behavior includes social pathology, defined as negative social behaviors that violate a system of norms and values and have a destructive impact on society on a larger scale. This study analyzed selected dysfunctional behavior and group socio-pathological phenomena existing in the police environment, which breaks down group ties and harms society at large. The study discusses such issues as extreme behavior in a professional situation, lack of readiness to oppose illegal influence, and mobbing.